2008
DOI: 10.1097/mcg.0b013e31811edcf7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Perihepatic Lymphadenopathy in Acute and Chronic Liver Disease

Abstract: Perihepatic lymphadenopathy is found in infectious and autoimmune liver diseases, but not in metabolic or toxic liver damage. The absence of perihepatic lymph nodes in acute liver failure should lead to intensive search for a toxic or metabolic cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 20 publications
1
29
0
5
Order By: Relevance
“…In a study conducted by Braden et al (15), it was concluded that periportal lymphadenopathy is common in infectious diseases and acute autoimmune diseases, and the absence of periportal lymph nodes in acute liver injury has led to a search for toxic and metabolic causes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted by Braden et al (15), it was concluded that periportal lymphadenopathy is common in infectious diseases and acute autoimmune diseases, and the absence of periportal lymph nodes in acute liver injury has led to a search for toxic and metabolic causes.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the prevalence of sonographic signs in patients with viral and acute hepatitis, ultrasound and computerized tomography scan (CT scan) studies have been investigated by some researchers (2,(13)(14)(15). Also, some other researchers have studied the efficacy of conventional ultrasound and Doppler in the diagnosis of acute hepatitis (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. eine intra-oder extrahepatische Gallenwegerweiterung, Tumoren oder Gefäßthrombosen) auszuschließen [133]. Abdominelle Lymphknoten sind in 40 -90 % der Patienten mit AIH darzustellen [134,135]. Es gibt jedoch keine AIH-spezifischen Ultraschallkennzeichen.…”
Section: Starke Empfehlung Starker Konsensunclassified
“…Zum Ausschluss obstruierender Gallenwegerkrankungen in der Initialdiagnostik soll ein abdomineller Ultraschall erfolgen [133]. Abdominelle Lymphknoten(vergrößerungen) bei Patienten mit PBC sind in 87 -97 % zu sehen [134,135], es gibt jedoch keine PBC-spezifischen Ultraschallkennzeichen. Die diagnostischen Genauigkeiten zur Detektion einer Zirrhose mittels B-Bild-Ultraschall liegen bei 78 bis 88 % und können durch Kombination mit der Scherwellenelastografie verbessert werden [136,137].…”
Section: Kommentarunclassified